Effects of photoperiod on growth performance and melanogenesis pathway for skin pigmentation of Malaysian red tilapia - Malambugi, Atuganile; Yu, Zhenzhen; Zhu, Wenbin; Wang, Lanmei; Song, Feibiao; Limbu, Samwel Mchele; Dong, Zaijie (Aquaculture research, 2020)
Farming of red tilapia is increasing rapidly. However, its commercial farming development is challenged by lack of clear information on genetic basis for skin colour and pigmentation differences due to environmental changes. This study investigated the effects of photoperiod (light:dark, L:D) on the growth and skin colour variation of Malaysian red tilapia. A total of 180 fish weighing 150.48 ± 0.44 g were reared under natural photoperiod (13L:11D, control), prolonged lightness (24L:0D) and prolonged darkness (0L:24D) in three replicates for 78 days. The weight gain of fish cultured under both prolonged light and darkness were significantly higher than fish under natural photoperiod. The tyrosinase level in ventral skin was significantly higher for fish cultured under prolonged darkness condition than in the other two photoperiod regimes. Contrary, the cysteine level in the dorsal skin was significantly higher in the fish cultured under natural photoperiod than in prolonged light and darkness. The relative mRNA expressions of SRY‐related HMG‐Box 10 (sox 10), tyrosine (tyr), tyrosine‐related protein 1 (tyrp‐1) and solute carrier family 7 member 11 (slc7a11) genes were significantly higher in ventral skin of fish under prolonged darkness than the other two photoperiods. This study demonstrates that photoperiod has an impact on melanogenesis and growth of red tilapia. Understanding the effects of photoperiod on genetic basis of red tilapia will help in selective breeding programme of the important economic traits for the development of commercial red tilapia farming.